The Smartphone Uses and Dependency Toward Emotional Intelligence on Generation Z - Setyanto, Aprilian; Franksiska, Rosaly (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2021)
Advances in smartphone technology can now help workers in almost everything, from aspects of communication, entertainment, education, and so on. In some cases, while in the office workers usually use their smartphone to relieve their work stress during working hours. This study aims to analyze the effect of smartphone use and dependence on workers' emotional intelligence. This research is a quantitative research using the correlation analysis technique. The population in this study is Generation Z who are already working. Sampling was done by using the purposive sampling technique, to obtain a sample of 106 respondents. Data was collected using an instrument in the form of a questionnaire. The data that has been collected is then analyzed using multiple regressions. The findings show that the regression equation for this study is Y = 0.043 – 0.07058(X1) + 0.883(X2) + e. Based on these equations, it can be concluded that the use of smartphone has a negative effect on the emotional intelligence of workers, while dependence on smartphone has a positive effect on the emotional intelligence of workers.